2014
DOI: 10.1097/ajp.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Matters

Abstract: Studies have associated chronic low back pain (cLBP) with grey matter thinning. But these studies have not controlled for important clinical variables (such as a comorbid affective disorder, pain medication, age, or pain phenotype), which may reduce or eliminate these associations. We conducted cortical thickness and voxel-based morphometry (VBM) analyses in 14 cLBP patients with a discogenic component to their pain, not taking opioids or benzodiazepines, and not depressed or anxious. They were age and gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In previous studies, Li et al28 reported that brain areas, including bilateral paracentral lobule and the right thalamus were activated by acupuncture treatments. Erpelding et al29 found that cortical thickening in the paracentral lobule correlated with higher sensitivity to cool stimulation, and an analogous cortical thickening in the right paracentral lobule was observed in individuals with chronic low back pain 30. Studies using transcutaneous electrical nerve stimulation reported that significant pain-related activation occurred in the S1, S2 regions and paracentral lobule 31.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, Li et al28 reported that brain areas, including bilateral paracentral lobule and the right thalamus were activated by acupuncture treatments. Erpelding et al29 found that cortical thickening in the paracentral lobule correlated with higher sensitivity to cool stimulation, and an analogous cortical thickening in the right paracentral lobule was observed in individuals with chronic low back pain 30. Studies using transcutaneous electrical nerve stimulation reported that significant pain-related activation occurred in the S1, S2 regions and paracentral lobule 31.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, similar atrophy and hypoactivity in sensory information transmission and processing regions were demonstrated in patients with chronic pain. 6 8 , 12 , 45 In discogenic LBLP patients, injuries to the surrounding nerves might affect or prevent the function/movement of the related regions, causing a decrease in the gray matter in the corresponding somatosensory regions. In contrast to other nonspecific low-back pain, discogenic LBLP might be attributable to a recognizable specific pathology associated with central vulnerability and/or sensitivity to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional alterations related to low-back pain or chronic back pain have been demonstrated using advanced neuroimaging techniques. Examples of these alterations include neuron metabolite abnormities; 5 cortical atrophy in the so-called “pain matrix”, including the S1/S2 regions, insula, and medial prefrontal cortex (mPFC); 6 , 7 cortical thinning in the “pain matrix” and pain-processing regions (trending in S1); 8 white matter microstructure damage in the corpus callosum and internal capsule; 9 11 hyper-activation in the mPFC after thermal stimulation 11 and activity in pain-associated regions (thalamus and cingulate cortex) following mechanical stimulation; 12 and highly consistent functional connectivity reorganization in several regions 11 , 13 17 with the exception of disrupted default mode network (DMN) connectivity. 14 16 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Although the broader pain literature generally suggests a correlation between clinical outcome measures and brain volume(31, 56, 57), studies specifically examining LBP reported no correlations between such outcomes and brain volume even in the presence of brain volume differences(36, 40). Such findings question the clinical relevance of the differences in brain volume reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller brain volumes have been reported in such neurodegenerative diseases as multiple sclerosis(21–23), Alzheimer’s disease(2426), and schizophrenia(2729), and also in chronic pain conditions like fibromyalgia(3032), complex regional-pain syndrome (33, 34), and chronic LBP(35, 36). To date, only a few structural brain imaging studies in people with chronic LBP(3542) have been completed.…”
Section: Introductionmentioning
confidence: 99%